CURRENT STATUS AND PROBLEMS OF RESEARCH ON THE MANAGEMENT OF HIGHER EDUCATION DEVELOPMENT IN THE INFORMATION ENVIRONMENT (American Journal of Pedagogical and Educational Research, 2023)
This article analyzes the current state and problematic areas of research on the management of the development of higher education in the context of informatization. Also, the study of trends in the development of higher education and the analysis of World models can make it possible to determine the need for fundamentally new approaches to managing its development in the context of the modernization of Higher Education, increase its effectiveness and relevance of its results.